Soybean protease inhibitors increase Bacillus thuringiensis subs. israelensis toxicity against Hypothenemus hampei = Inhibidores de proteasas de soya incrementan la toxicidad de Bacillus thuringiensis subs. israelensis contra Hypothenemus hampei - Mesén Porras, Esteve Alonso 1990-
Introduction. The coffee berry borer (Hypothenemus hampei Ferrari, CBB) is one of the most devastating pests on coffee plantations around the world. Although CBB is susceptible to the effect of δ-endotoxins of Bacillus thuringiensis subs. israelensis (Bti) at laboratory level, the efficacy of this control method is poor in the field, presumably due to the inactivation by digestive proteases different to those required for protoxin activation. Objective. To study whether the addition of a soybean flour extract enriched with protease inhibitors (PI), mixed with Bti crystals and spores (Bti-sc) in an artificial diet, could improve the toxicity of Bti against CBB. Materials and methods. This study was performed in San José, Costa Rica, between 2012 and 2013. A set of adult female CBB insects was exposed to a mixture containing different concentrations of a partially purified soybean meal extract with active PI and lyophilized Bti-sc, and were tested through a bioassay in artificial diet to estimate the sub-lethal concentration (LC50). The mortality results were validated by observing the dissected midgut, whose ultrastructure was analyzed by transmission electron microscopy. Results. The soybean extracts partially degraded the Bti-sc complex, it reduced its LC50 by almost four times (from 1.135 to 0.315 μg μl-1) and enhanced CBB mortality in a concentration-dependent manner. Histological analyses of the midgut confirmed this synergistic effect, since severe epithelial damage to the intestinal epithelium of CBB exposed to Bti-sc + PI was visualized compared to Bti-sc alone. Conclusions. The combination of a soybean extract enriched in PI and Bti-sc enhanced the mortality effect over CBB, which was confirmed by the midgut collapse. Soybean flour is a cost-effective supplement that could increase Bti effectiveness against CBB and delay the appearance of biological resistance.